Production of diaspores at the landscape level regulates local colonization: an experiment with a spore‐dispersed moss. Issue 6 (23rd January 2014) - Lönnell, Niklas; Jonsson, Bengt Gunnar; Hylander, Kristoffer
<x xml:space="preserve">Abstract</x> Effective dispersal is crucial to species inhabiting transient substrates in order for them to be able to persist in a landscape. Bryophytes, pteridophytes, lichens and fungi all have wind‐dispersed small diaspores and can be efficiently dispersed if their diaspores reach air masses above canopy height. However, empirical data on dispersal over landscape scales are scarce. We investigated how the colonization of an acrocarpous clay‐inhabiting pioneer moss, Discelium nudum, varied between sites that differed in connectivity to potential dispersal sources at spatial scales from 1 to 20 km in a region in northern Sweden. We recorded the colonization on ˜25 introduced clay heaps at each of 14 experimental sites some months after the dispersal period. The colonization rate ranged from 0–82% and had a statistically significant relationship with a proxy for potential habitats (amount of clay‐dominated soil) in a buffer of 20 km radius surrounding the experimental sites (and also weakly with the amount of substrate in a 10 km buffer). There were no significant relationships between colonization rate and connectivity at smaller scales (1 and 5 km). We made a rough estimate of the number of spores available for dispersal in a landscape, given the amount of clay‐dominated soil, by recording the number of Discelium nudum colonies in two 25 × 25 km landscapes. The estimated available spore numbers in the different 20 km buffers were of the same order of magnitude as the deposition densities at the experimental sites calculated from the colonization rates. The results suggest that the spores of species with scattered occurrences and small diaspores (25 μm) in open landscapes can be deposited over extensive areas, at rates high enough to drive colonization patterns. This also implies that regional connectivity may be more important than local connectivity for these kinds of species.